(untitled) (Jurnal Adabiya, 2025)
The main focus of this paper is to look at the views of a fair society towards the implementation of Islamic law in Aceh in various existing regulations, especially the appeal of the regent of Aceh Besar which requires flight attendants to dress in Muslim women at the Sultan Iskandar Muda (SIM) Airport. So far, the image that has been built through various narratives and unbalanced literacy, especially carried out by supporters of gender equality and human rights in their various studies, has always stated that women are restrained, marginalized and not given sufficient space in the domestic and public spheres. This study uses a qualitative descriptive approach, with data collected through observation, interviews and document review which are then refined by data analysis. This research finds that academics, ulama, policy makers and women "victims" have different views on the image of Islamic Sharia in Aceh; especially to the appeal for stewardess to wear Muslim clothing at the SIM airport which has been built as if it were an act of discrimination against women, even though all of this is a concrete effort to protect women. However, there are still many applications in the field, especially regarding socialization procedures that must and need to be considered. For this reason, continuous and comprehensive and soothing socialization involves bureaucrats, academics, scholars, community leaders and women through comprehensive socialization, especially through various writings in print media, such as in journals, magazines, newspapers, pamphlets, banners and other printed media as well as through electronic media, such as radio, television, Facebook, Instagram, YouTube, and so on.ABSTRAK Fokus utama tulisan ini adalah untuk melihat pandangan masyarakat yang adil terhadap Pemberlakuan Syariat Islam di Aceh dalam berbagai regulasi yang ada, khususnya terhadap himbauan Bupati Aceh Besar yang mewajibkan Pramugari untuk Berbusana Muslimah di Bandara Sultan Iskandar Muda (SIM) Aceh Besar. Selama ini image yang dibangun melalui berbagai narasi dan literasi yang tidak seimbang, terutama yang dilakukan oleh kalangan para pendukung kesetaraaan gender dan HAM dalam berbagai penelitian mereka yang selalu menyatakan perempuan dikekang, dimarjinalkan dan tidak diberikan ruang yang cukup di ranah domestik dan publik. Penelitian ini menggunakan pendekatan deksriptif kualitatif, dengan data yang dikumpulkan melalui observasi, wawancara dan telaah dekumen yang kemudian disempurnakan dengan analisis data. Penelitian ini mendapat hasil bahwa para akademisi, ulama, pengambil kebijakan dan para perempuan “korban” memiliki pandangan yang berbeda atas image Syariat Islam di Aceh; khususnya terhadap Himbauan Pramugari Wajib Berbusana Muslimah di Bandara SIM Aceh Besar yang selama ini dibangun seolah-olah sebagai tindakan diskriminasi terhadap kaum perempuan, padahal semua itu adalah sebagai upaya kongkrit perlindungan terdahap kaum perempuan. Hanya saja, aplikasi di lapangan, terutama menyangkut tata cara sosialisasi masih banyak yang harus dan perlu dipertimbangan. Untuk itu, sosialisasi yang kontinyu dan konprehensif dan menyejukkan dengan melibatkan birokrat, akademisi, ulama, tokoh masyarakat dan kaum perempuan melalui sosialisasi yang konprehensif, terutama melalui berbagai tulisan di media cetak, seperti di jurnal, majalah, rurat kabar, pamphlet, benner dan media cetak lainnya serta melalui media elektronik, seperti radio, televisi, fesbuk, instragram, youtube, dan lain sebagainya.